Virtual reality game, game engine and XNA framework - Basori, Ahmad Hoirul (Penerbit UTM, 2007)
Virtual reality (VR) has become the main consideration to simulate real interaction into virtual environment. On the other hand, games also hold important rules to handle military training, medical systems and education known as Serious Game (Chen 2006). The combination between virtual reality and game called Virtual Reality Game (VRG) has given a new opportunity to merge entertainment aspect with educational material (Virvou et al. 2006; Rossou et al. 2004).